Poverty's no hindrance to success - New Sunday Times, (2004)
Home used to be on a Felda oil palm estate in Kota Tinggi but Suriana Sabri, poverty was no hindrance to academic excellence and eventually, success. Perhaps the fact that she was the only child in a family of seven siblings who made it to university provided another impetus for her to strive for excellence.